How to Best Develop and Deliver Generic Long-Term Condition Rehabilitation Programmes in Rural Settings: An Integrative Review - Wilkinson, Amanda; Higgs, Chris; Stokes, Tim; Dummer, Jack; Hale, Leigh (Frontiers in Rehabilitation Sciences, 2022)
People living rurally frequently experience health disparities especially if living with a long-term condition (LTC) or multi-morbidity. Self-management support is a key component of LTC management and commonly included in rehabilitation programmes to enhance ability to self-manage health and encourage physical activity. Such programmes are however often disease focussed and despite evidence for their effectiveness, are not always feasible to deliver in rural settings. Generic programmes are arguably more optimal in the rural context and delivery can be face to face or remotely (via telehealth). The aim of this integrative review was to collate and present international evidence for development, delivery, integration and support of generic LTC rehabilitation programmes delivered rurally or via the internet. Electronic databases were systematically searched using MeSH terms and keywords. For inclusion, articles were screened for relevance to the aim, and practical information pertaining to the aim were extracted, charted, and organised deductively into themes of development, delivery, integration and support. Within each theme, data were synthesised inductively into domains (Theoretical, Contextual, Interpersonal, and Technological and Programme aspects). Fifty-six studies were included. Five studies contributed information about community based programmes delivered via the internet. Development was the only theme where information populated all domains. The theme of Support only had information pertaining to the domain of Contextual aspects. Our review has drawn together a large body of diverse work. It has focused on finding practical information pertaining to the best ways to develop, deliver, integrate and support a community-based generic rehabilitation programme for people living with long-term health conditions, delivered rurally and/or potentially via the internet. Practical suggestions were thematically organised into domains of theoretical, contextual, interpersonal, and technological and programme aspects. While the findings of this review might appear simple and self-evident, they are difficult to enact in practice.